Primary Molecular Disorders and Secondary Biological Adaptations in Bartter Syndrome. (20th September 2011) - Deschênes, Georges; Fila, Marc
Abstract : Bartter syndrome is a hereditary disorder that has been characterized by the association of hypokalemia, alkalosis, and the hypertrophy of the juxtaglomerular complex with secondary hyperaldosteronism and normal blood pressure. By contrast, the genetic causes of Bartter syndrome primarily affect molecular structures directly involved in the sodium reabsorption at the level of the Henle loop. The ensuing urinary sodium wasting and chronic sodium depletion are responsible for the contraction of the extracellular volume, the activation of the renin-aldosterone axis, the secretion of prostaglandins, and the biological adaptations of downstream tubular segments, meaning the distal convoluted tubule and the collecting duct. These secondary biological adaptations lead to hypokalemia and alkalosis, illustrating a close integration of the solutes regulation in the tubular structures.